THE CONVERSATIONAL INFERENCE IN CEMARA’S FAMILY BY ARSWENDO ATMOWILOTO - Lia Endang Suryani; Putri Giyanwati Praditya (Universitas Stikubank (UNISBANK) Semarang, 2017)
Novel is a work of fiction prose written in a narrative and usually written in story form. The word Novel is comes from the Italian